MODEL COOPERATIVE SCRIPT PADA PEMBELAJARAN BAHASA INGGRIS ASPEK BERBICARA: SEBUAH HIPOTESIS - Siti Nurhayati (Balai Diklat Keagamaan Bandung, 2021)
This article aims to hypothetically reveal the cooperative script model. The cooperative script model is believed to solve passive learning problems particularly in speaking. The model aims to develop social skills, teaching students to be cooperative and collaborative. In its application, students were encouraged to bravely collaborating in pairs on expressing new ideas or material being studied, as well as providing opportunities for them to bring out new creativities so they are motivated to work harder on achieving learning goals. In addition, when cooperative relationships occured, the students could appreciate their friends’ ideas, not the other way around. This study uses library research method by concocting hypotheses related to cooperative script model applied in Speaking. The English teacher can also obtain knowledge and description for appllying the model. It is also expected that the teachers are able to develop cooperative script model in other English language skills, so that students can communicate for expressing their daily needs. Keywords: Application; Cooperative Script Model; English Subject; Speaking